The Anticoagulant and Nonanticoagulant Properties of Heparin - Beurskens, Danielle M. H.; Huckriede, Joram P.; Schrijver, Roy; Hemker, H. Coenraad; Reutelingsperger, Chris P.; Nicolaes, Gerry A. F. (Thrombosis and Haemostasis, 2020)
Heparins represent one of the most frequently used pharmacotherapeutics. Discovered around 1926, routine clinical anticoagulant use of heparin was initiated only after the publication of several seminal papers in the early 1970s by the group of Kakkar. It was shown that heparin prevents venous thromboembolism and mortality from pulmonary embolism in patients after surgery. With the subsequent development of low-molecular-weight heparins and synthetic heparin derivatives, a family of related drugs was created that continues to prove its clinical value in thromboprophylaxis and in prevention of clotting in extracorporeal devices. Fundamental and applied research has revealed a complex pharmacodynamic profile of heparins that goes beyond its anticoagulant use. Recognition of the complex multifaceted beneficial effects of heparin underscores its therapeutic potential in various clinical situations. In this review we focus on the anticoagulant and nonanticoagulant activities of heparin and, where possible, discuss the underlying molecular mechanisms that explain the diversity of heparin's biological actions.
Keywords: heparin; anticoagulation; metastasis; inflammation